Concomitant tracheal and subcutaneous glomus tumor: Case report and review of the literature. (2015) - Fernandez-Bussy, Sebastian; Labarca, Gonzalo; Rodriguez, Macarena; Mehta, Hiren J.; Jantz, Michael
Abstract: Glomus tumors are unusual and generally benign neoplasms mainly found in subungeal areas. We describe a case of concomitant subcutaneous and tracheal glomus tumor that underwent successful endoscopic resection. A 48-year old male with a left forearm subcutaneous mass presented with hemoptysis. A chest CT scan demonstrated a polypoid tracheal lesion. He underwent a bronchoscopic resection. A biopsy revealed a glomus tumor, which was the same type of neoplasm that was found on the forearm biopsy. Glomus tumors are rarely found in the respiratory tract. Only 49 cases have been described. The majority of the glomus tumors arise from the lower posterior tracheal wall with no extraluminal extension. Bronchoscopic resection has been successfully used. Glomus tumors should be included in the differential diagnosis of tracheobronchial lesions. Bronchoscopic resection and adjuvant radiotherapy are valid treatment options. This is the first report of concomitant subcutaneous and tracheal glomus tumor, as well as the first reported airway glomus tumor, in Latin America. As part of this study, we also perform a literature review.